The Influence of Financial Literacy, Salary, and Work Environment on Employee Job Satisfaction with Work Motivation as a Moderating Variable - Sinaga, Royanti; Saragih, Nahar Maganda; Hazimah, Zulfa; Elyana, Mahlian (Jurnal Transformasi Digital dalam Ekonomi, Bisnis, dan Manajemen, 2025)
This study aims to analyze the effect of financial literacy, salary, and work environment on employee job satisfaction with work motivation as a moderating variable. The study was conducted at the Regional Development Planning Agency (Bappeda) of Deli Serdang Regency with a quantitative approach and census method on 89 respondents. Data processing used SmartPLS to test the structural model. The results showed that financial literacy had a positive and significant effect on work motivation, but did not have a significant effect on job satisfaction. Salary had a significant positive effect on job satisfaction, but was not significant on work motivation. The work environment had a significant negative effect on job satisfaction, but was not significant on work motivation. Meanwhile, work motivation did not show a significant effect on job satisfaction. These findings indicate that increasing financial literacy and perceptions of fair salary can increase employee motivation and job satisfaction, while poor work environment conditions can decrease job satisfaction.